Occupational therapy pre-discharge HOme VIsits for patients with a Stroke (HOVIS): results of a randomised controlled trial - Drummond, A.E.R.; Whitehead, P.; Fellows, K.; Sprigg, Nikola; Sampson, Christopher James; Edwards, Claire; Lincoln, Nadina (SAGE, 2012)
Objective To conduct a randomised controlled trial (RCT) of occupational therapy predischarge home visits for people after stroke in order to assess the feasibility of a definitive trial. Design Two studies; a randomised controlled trial and a cohort study. We randomised eligible patients for whom there was clinical uncertainty about the need to conduct a home visit in to an RCT; patients for whom a visit was deemed ‘essential’, were enrolled into a cohort study. Setting Stroke rehabilitation unit of teaching hospital Participants 126 participants hospitalised following recent stroke. Interventions Pre-discharge home visit with an occupational therapist or structured hospital based interview with occupational therapist. Main outcome measures The primary objective was to collect information on the feasibility of an RCT, including eligibility criteria, consent procedures, control intervention, and outcome assessments. The primary outcome measure was the Nottingham Extended Activities of Daily Living scale (NEADL) at one month after discharge from hospital. Secondary outcomes were measures of activities of daily living, mood, quality of life and costs at one week and one month following discharge. Results Ninety- three people were allocated to the RCT. Of these 47 were randomised to intervention and 46 to the control. Thirty-three patients were enrolled into the cohort study and received a home visit. Forty-one (87%) participants in the RCT intervention group and 29 (88%) participants in the cohort study received the intervention. There were no significant differences in outcome between the groups in the RCT for the primary outcome measure (performance in extended activities of daily living) at one month. The average cost of a home visit was £208 (£183 for those in the RCT and £243 for those in the cohort study). The average cost of the interview for the control group was £75. Conclusion Our main finding was that recruitment to the trial was feasible and no safety issues were raised. A trial is warranted given the resource implications of pre- discharge occupational therapy home visits.